From translation models and model translations to translation as a model: some implications for translation studies and teaching - Mallet, Brian (Íkala, Revista de Lenguaje y Cultura, 1999)
The development of translation studies in recent years has allowed the discipline to acquire a new sense of identity. The focus has shifted away from the translation "product" to the translation "process*. The implications of these developments and trends need to be taken into account at curricular and methodological levels in the establishment of university programmes in translation studies. The quality of translation teaching can be enhanced by seeing translation as a metaphor and model of its own right and as an open-ended process which is democratic, participatory and creative.